2022
DOI: 10.31095/podium.2022.41.9
|View full text |Cite
|
Sign up to set email alerts
|

Análisis informétrico del metaverso en canales y vídeos hispanoparlantes de YouTube

Abstract: El objetivo es caracterizar el impacto en términos de visualizaciones, likes y comentarios recibidos para vídeos sobre el metaverso y términos relacionados, publicados y difundidos a través de YouTube en idioma español; y finalmente, categorizar los canales a través de los cuales se han publicado dichos vídeos relacionados a este fenómeno. Para el estudio, se utilizó un análisis informétrico descriptivo, cuantitativo y transversal sobre 5.479 vídeos publicados hasta el 10 de abril del 2022 y 822 canales de You… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
0
5
0
5
Order By: Relevance
“…The immersion level the metaverse offers in a conceptual and semiotic world beyond what is possible with any other technology, providing individuals with a feeling of presence and connection with other users in a real and exciting manner. When applied to education (Menezes et al, 2019;Ochoa & Ortíz, 2018;Garzón, 2022), this first-person experience has been shown to increase the comprehensive abilities of students (Dwivedi et al, 2022). Furthermore, it is important to note that game-based learning may not be suitable for all learning objectives and subjects.…”
Section: Learned Lessonsmentioning
confidence: 99%
See 2 more Smart Citations
“…The immersion level the metaverse offers in a conceptual and semiotic world beyond what is possible with any other technology, providing individuals with a feeling of presence and connection with other users in a real and exciting manner. When applied to education (Menezes et al, 2019;Ochoa & Ortíz, 2018;Garzón, 2022), this first-person experience has been shown to increase the comprehensive abilities of students (Dwivedi et al, 2022). Furthermore, it is important to note that game-based learning may not be suitable for all learning objectives and subjects.…”
Section: Learned Lessonsmentioning
confidence: 99%
“…To increase its reach within the educational field, the company invested USD 10 million to develop three educational games focused on robotics, space exploration, IT, biomedical science, and engineering which will be distributed for free in schools in several countries (Dean, 2022). Given the current trend, it is likely that, in the next years, we will observe an increase in the use of educational games and platforms, and a growing interest in the use of metaverses for education (Garzón, 2022).…”
Section: Learned Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…A metaverse is a virtual environment capable of simulating both a real physical environment and a digital world (Chediak, 2023;Vallejos, 2023) whose application to the educational field focuses on offering virtual education solutions generating new collaborative learning models, and thereby encouraging interactive student participation (Ruiz-Campo et al, 2022). Currently, the metaverse is considered as a universal, unified and interoperable 3D space with the capacity for immersion, corporeality and persistence (Mendiola, 2022;Quiroz et al, 2023). In this way, immersiveness means that users are immersed in the virtual world and can feel the experience, on the other hand, corporeality allows users to be represented by avatars that personify the user experience and persistence means that continues execution, even without being connected (Barráez-Herrera, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The metaverse is conceptualized as fictional constructions in which the participants interact through avatars, trying to reproduce real life in a virtual metaphor environment, without space-time limitations (Felip, 2023;Hurtado-Chong et al, 2022;Vidal, 2022). The metaverse is a record of the life of its users, where they interact in a mirror world with augmented reality and virtual reality; this space is oriented toward reality, but focused more on the virtual (Quiroz, 2022). In addition, the metaverse supposes the development of a network of virtual environments in which users can carry out different activities in an immersive way (Arias & Alexandra, 2016;Buitrago & Yesid, 2016;Herrero, 2023;Ramallal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%